Translating Directives: Subtitling Strategies and Acceptability in The End Of The F***ing World Season One - Brylliant, Alief Nino; Kholifah, Asrofin Nur; Yulianita, Nadia Gitya (Universitas Sebelas Maret, 2025)
This research analyzed the directive illocutionary acts, translation strategies, and their acceptability in Alyssa’s utterances in The End of the F***ing World Season 1. Using Searle’s (1969) directive illocutionary act theory, Gottlieb’s (1992) translation strategies, and Nababan et al.’s (2012) acceptability assessment, this qualitative study collected data through questionnaires with rater feedback. The findings identified 59 directive acts, with commanding (33) as the most frequent, followed by asking (14), suggesting (9), inviting (2), and prohibiting (1). The most used subtitling strategies were transfer (31), condensation (10), and paraphrase (9), ensuring fidelity and fluency. Acceptability results showed 57 instances as acceptable and only 2 as less acceptable. The predominance of transfer, condensation, and paraphrase confirmed their effectiveness in maintaining Alyssa’s character traits and enhancing subtitle quality.